Effects of light feedback on swimming performance - Buresta, A. (FINA Golden Coaches Clinic 2016, 2016)
Alessandro Buresta (Founder of Indico Technologies) talks about "Effects of light feedback on swimming performance" at the FINA Golden Coaches Clinic 2016, December, 4-5th.